A Visual Narration of Hells in Buddhism and Islam - Ary Budianto (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2011)
The visualization of the Hell’s Tortures both in Buddhism and in Islam is exactly similar. However, their kind of ‘theological’ tendencies may result different outcome. By comparing the visual narration of the Buddhism and Islamic comic books dealing with hell illustrations, I made an‘imaginary’ dialogue between the concept and visuality of hells tortures that exist in both traditions, and see the impact on how far a sincere dialogue could be achieved in these two religious people. During this comparison, I found that both Buddhism and Islam in Java had ever made such an interesting dialogue.Keywords: Hell tortures, Islam-Buddhism comparison, encounter of Java-IndonesiaDOI: 10.15408/ref.v13i1.995